2011
DOI: 10.1080/03670244.2011.620877
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Variables and Obesity-Risk-Reduction Behaviors in Chinese Americans

Abstract: The objective of this study was to utilize social-psychological theories to explain obesity-risk-reduction behaviors. A questionnaire based on the health belief model and theory of planned behavior was administered to a convenience sample of 300 Chinese Americans in the New York metropolitan area. Psychosocial variables accounted for 40.4% of the variance of obesity-risk-reduction behaviors. Self-efficacy, behavioral intention, and perceived benefits emerged as most influential variables. Forty-eight percent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Knowledge The results of the current study converge with previous work that has been conducted in this fi eld, e.g., behavioral intention is a demonstrated correlate of blood pressure control behaviors such as physical activity in Chinese Americans ( Liou, Bauer, & Bai, 2011 ) while self-effi cacy has been shown to account for much of the variance in behavioral intention to reduce dietary fat ( Liou & Contento, 2001 ). Unique to these data is the demonstration of these relationships in an urban Korean-American population.…”
Section: Attitudes and Beliefssupporting
confidence: 85%
“…Knowledge The results of the current study converge with previous work that has been conducted in this fi eld, e.g., behavioral intention is a demonstrated correlate of blood pressure control behaviors such as physical activity in Chinese Americans ( Liou, Bauer, & Bai, 2011 ) while self-effi cacy has been shown to account for much of the variance in behavioral intention to reduce dietary fat ( Liou & Contento, 2001 ). Unique to these data is the demonstration of these relationships in an urban Korean-American population.…”
Section: Attitudes and Beliefssupporting
confidence: 85%
“…However, intention emerged as an additional contributing factor in predicting behavior in the NY participants. These findings from the LA sample provides confirmatory data, as compared with the NY sample, in the importance of self-efficacy, intention, and attitude in contributing to obesity risk reduction behaviors among Chinese Americans [19]. Similarly, Liou and Contento's study of dietary fat reduction behaviors in Chinese Americans identified the importance of selfefficacy in predicting behavioral outcomes [24].…”
Section: Discussionsupporting
confidence: 55%
“…The purpose of this study was to ascertain obesity risk reduction behaviors and their psychosocial determinants among a convenience sample of Chinese Americans residing in Los Angeles (LA) County, California and to compare the results to Chinese Americans living in the New York (NY) metropolitan area. A similar study of New York area Chinese Americans was previously completed and published by the same researchers [19]. To our knowledge, this breakthrough study marks the first West and East Coast comparative analysis of obesityrelated beliefs and behaviors among Chinese Americans.…”
Section: Theoretical Frameworkmentioning
confidence: 85%
See 2 more Smart Citations